2018
DOI: 10.5603/arm.a2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria Strains Isolated from Patients between 2013 and 2017 in Poland. Our Data with Respect to the Global Trends

Abstract: Introduction: During the last decades the prevalence of NTM infections has increased, especially in developed countries. The aim of the study was to provide an overview on all NTM isolated from clinical samples in Poland between 2013 and 2017. Material and methods: The study comprised 2799 clinical specimens, mostly respiratory accessed in the reference laboratory of National Tuberculosis and Lung Diseases Research Institute in Warsaw and in the Wielkopolska Center of Pulmonology and Thoracic Surgery, Poland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…As in other countries, in Poland also Kwiatkowska et al . ( 32 ) observed an increased frequency of NTM isolated from clinical samples. Several isolates in the present study, namely M. abscessus , M. chelonae , M. fortuitum , M. gordonae , M. marinum , M. mucogenicum , M. neoaurum , M. peregrinum and M. szulgai , were also identified by Kwiatkowska et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other countries, in Poland also Kwiatkowska et al . ( 32 ) observed an increased frequency of NTM isolated from clinical samples. Several isolates in the present study, namely M. abscessus , M. chelonae , M. fortuitum , M. gordonae , M. marinum , M. mucogenicum , M. neoaurum , M. peregrinum and M. szulgai , were also identified by Kwiatkowska et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several isolates in the present study, namely M. abscessus , M. chelonae , M. fortuitum , M. gordonae , M. marinum , M. mucogenicum , M. neoaurum , M. peregrinum and M. szulgai , were also identified by Kwiatkowska et al . ( 32 ) in human clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, an increased number of isolates of NTM has been noticed. Mycobacterium kansasi , Mycobacterium avium , and Mycobacterium xenopi belong to the most often recognized and well-known mycobacteria [ 7 ]. Initially, the enormous interest in Mycobacterium chimaera was associated with patients who underwent cardiac surgeries with extracorporeal circulation [ 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…An NTM Network European Trials Group collaborative study showed that of all NTM isolates from pulmonary samples, M. szulgai was identified depending on the geographic region from 0% in Africa to 0.77% in Northern Europe [ 8 ]. In Poland, between 2013 and 2017, of 2799 NTM isolates, 12 (0.43%) M. szulgai cases were recorded [ 10 ].…”
Section: Discussionmentioning
confidence: 99%